Geographical analysis of Peach Trees Cultivation in Wasit Governorate - خلود حيدر لازم م.م. (lark, 2020)
Abstract The fruit of peach trees is an important and essential part of human food, as man has known its importance since ancient times and with its elevation of civilization ladder and its high standard of living, as these trees occupied a distinguished place in their food and their need increased, so he began looking for new methods to increase their production to meet his requirements, the study aims to Knowing the variation in the number of peach trees in Wasit Governorate, and the extent to which natural, human and living factors influence their variations from one region to another. Based on this, a geographical analysis of peach trees in Wasit Governorate was studied to find out the most important ways for the success and failure of this cultivation in the study area, The researcher relied on government data by the agricultural people and the Wasit Agriculture Directorate and then used the statistical analysis and the cropping and descriptive approach that strengthened with maps the extent of variation in the distribution of these trees affected by natural factors as the surface of the study area which is part of the sedimentary plain is characterized by extensibility and its suitability for planting these trees, The climate also has an effect on peach trees, especially the light and temperatures that both require, according to the requirements of these trees. Also, rain, wind, and dust storms cause loss of production as a result of burning parts of the leaf as well as closing the openings, and that knowledge Consciousness Primers that you need these trees.